Double‐stranded RNAs induce a pattern‐triggered immune signaling pathway in plants. Issue 3 (31st March 2016) - Niehl, Annette; Wyrsch, Ines; Boller, Thomas; Heinlein, Manfred
Summary: Pattern‐triggered immunity (PTI) is a plant defense response that relies on the perception of conserved microbe‐ or pathogen‐associated molecular patterns (MAMPs or PAMPs, respectively). Recently, it has been recognized that PTI restricts virus infection in plants; however, the nature of the viral or infection‐induced PTI elicitors and the underlying signaling pathways are still unknown. As double‐stranded RNAs (dsRNAs) are conserved molecular patterns associated with virus replication, we applied dsRNAs or synthetic dsRNA analogs to Arabidopsis thaliana and investigated PTI responses. We show that in vitro‐ generated dsRNAs, dsRNAs purified from virus‐infected plants and the dsRNA analog polyinosinic–polycytidylic acid (poly(I:C)) induce typical PTI responses dependent on the co‐receptor SOMATIC EMBRYOGENESIS RECEPTOR‐LIKE KINASE 1 (SERK1), but independent of dicer‐like (DCL) proteins in Arabidopsis. Moreover, dsRNA treatment of Arabidopsis induces SERK1‐dependent antiviral resistance. Screening of Arabidopsis wild accessions demonstrates natural variability in dsRNA sensitivity. Our findings suggest that dsRNAs represent genuine PAMPs in plants, which induce a signaling cascade involving SERK1 and a specific dsRNA receptor. The dependence of dsRNA‐mediated PTI on SERK1, but not on DCLs, implies that dsRNA‐mediated PTI involves membrane‐associated processes and operates independently of RNA silencing. dsRNA sensitivity may represent a useful trait to increase antiviral resistance in cultivated plants.